Geronimo Stilton reporter. 19, Cheese connection - Stilton, Geronimo; Costa, Davide (Stilton, Geronimo. Geronimo Stilton reporter, 2025)
"New Mouse City is having a cheese shortage and the residents are after every scrap they can find. It's chaos! Can criminal mastermind, Mouse Caponi, have something to do with this? And who is Marty Mimolette? Geronimo is determined to find out!" --